2011
DOI: 10.1089/scd.2010.0279
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Zinc Fingers and Homeoboxes 3 on the Regulation of Mesenchymal Stem Cell Osteogenic Differentiation

Abstract: We propose zinc fingers and homeoboxes 3 (ZHX3) as new osteogenic markers for mesenchymal stem cells (MSC). ZHX3 mRNA expression was upregulated within 1-6 h after incubation of MSCs in the osteogenic induction medium, and reached maximum levels after 24 h of incubation. Two to 4 days later, ZHX3 mRNA levels had decreased sharply. Maximal mRNA levels were 3- to 5-fold higher than those in the undifferentiated state. In contrast, Runt-related transcription factor2 (RUNX2) mRNA expression was downregulated at 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…These results indicated that quercetin could not only promote the proliferation of rBMSCs but also enhance osteogenic differentiation at various stages, especially at the middle and late stages; additionally, the concentration of 2 μM was found to be the optimum concentration. However, previous studies have shown that the cellular morphology is one of aspects, which can influence the osteogenic differentiation of MSCs [ 61 63 ]; the other studies also showed that some transcription factors (TFs) and Chinese medicine, such as zinc fingers and homeoboxes 3 (ZHX3), Runx2 and Tinospora cordifolia, could promote the osteogenic differentiation of MSCs by regulating the gene expression and secretion of osteogenic markers without significant effect on the cellular morphology [ 64 66 ]. Present study also showed that quercetin could stimulate the osteogenic differentiation of rBMSCs by promoting the gene expression and secretion of osteogenic markers without obvious effect on the cellular morphology.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that quercetin could not only promote the proliferation of rBMSCs but also enhance osteogenic differentiation at various stages, especially at the middle and late stages; additionally, the concentration of 2 μM was found to be the optimum concentration. However, previous studies have shown that the cellular morphology is one of aspects, which can influence the osteogenic differentiation of MSCs [ 61 63 ]; the other studies also showed that some transcription factors (TFs) and Chinese medicine, such as zinc fingers and homeoboxes 3 (ZHX3), Runx2 and Tinospora cordifolia, could promote the osteogenic differentiation of MSCs by regulating the gene expression and secretion of osteogenic markers without significant effect on the cellular morphology [ 64 66 ]. Present study also showed that quercetin could stimulate the osteogenic differentiation of rBMSCs by promoting the gene expression and secretion of osteogenic markers without obvious effect on the cellular morphology.…”
Section: Discussionmentioning
confidence: 99%
“…By screening the UCB dataset from TCGA, we identified that zinc finger and homeobox 3 ( ZHX3 ) was either gained or amplified in 59.6% (243/408) of patients with UCB. The ZHX3 gene, which is mapped to chromosome 20q12, has been found to be associated with many kinds of biological processes, such as cell differentiation and metabolism 8,9 . It has been suggested that ZHX3 is a ubiquitous transcriptional repressor expressed in human cells and tissues 10 .…”
Section: Introductionmentioning
confidence: 99%
“…From their identification, ZHX family members have been identified as transcriptional repressors through interacting with the α-subunit of the nuclear factor Y (NF-YA) and forming homodimers and heterodimers with each other 913. Increasing evidence has revealed that ZHX factors are major transcriptional mediators involved in the events including development and differentiation of hematopoietic cells, maintenance of neural progenitors and osteogenic differentiation of mesenchymal stem cells 8,14,15. Dysregulation of ZHX factors has been found to be correlated with initiation and progression of diverse diseases such as neurological, hematological and glomerular diseases 8,16,17.…”
Section: Introductionmentioning
confidence: 99%